Pengembangan Sistem Informasi Web MTFSales menggunakan Teknologi ReactJS dan Geolocation untuk Memantau Kinerja Karyawan Sales (Studi Kasus: Mandiri Tunas Finance) - Aditya Dwi Wicaksono; Buce Trias Hanggara; Tibyani Tibyani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
In sales activities, sales employees have an important role because their main job is to sell company products or services to buyers. For this reason, it is necessary to maintain several dominant factors that can affect the performance of a sales employee, such as discipline, motivation, and responsibility. In this digital era, technology can be used as a tool to monitor employee performance. One company that needs this technology is Mandiri Tunas Finance (MTF). Therefore, the researcher developed an MTFSales information system to monitor the performance of sales employees with the aim of knowing the results of needs analysis, design, implementation, and testing of the MTFSales. In this development, the waterfall software development method is used, because all MTFSales requirements have been defined at the requirements analysis stage by brainstorming with stakeholders from MTF with the results of identifying 3 actors, 7 functional requirements, and 1 non-functional requirement. MTFSales is developed using ReactJS and assisted with geolocation technology to get user's location. From the results of the test using the system usability scale (SUS), 63,125 points were obtained, the SUS test was classified as Grade D, with an Adjective Rating of OK, and an Acceptability Range of marginal value. Based on the results of functional testing, the MTFSales web information system gets a success value of 100% of all the functionality that has been defined.